(3efGbH CHj GdYHGS GdTHJjs - (3jhSa Hf jMji Hf YjSi Hf YHO GdQMef GdJGOdj, CHh GdMLGL, GdeYQha HGHf GdnqRnqjGJ,J (B627 (3g` s
(3ChdgG (B:s
(3SeYfG ef abQGFg hUMGHg GdPjf TgOhG HQcJg Vi Gddg Yfg ai MjGJg hGTJgQJ cQGeGJg HYO haGJg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B205s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B257 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B343s
(3Odjd eDQN GdeZQH (B- (3U (B257 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B429 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdJGQjNs